Draft genome analysis provides insights into the fiber yield, crude protein biosynthesis, and vegetative growth of domesticated ramie (Boehmeria nivea L. Gaud). (15th November 2017) - Liu, Chan; Zeng, Liangbin; Zhu, Siyuan; Wu, Lingqing; Wang, Yanzhou; Tang, Shouwei; Wang, Hongwu; Zheng, Xia; Zhao, Jian; Chen, Xiaorong; Dai, Qiuzhong; Liu, Touming
Abstract: Plentiful bast fiber, a high crude protein content, and vigorous vegetative growth make ramie a popular fiber and forage crop. Here, we report the draft genome of ramie, along with a genomic comparison and evolutionary analysis. The draft genome contained a sequence of approximately 335.6 Mb with 42, 463 predicted genes. A high-density genetic map with 4, 338 single nucleotide polymorphisms (SNPs) was developed and used to anchor the genome sequence, thus, creating an integrated genetic and physical map containing a 58.2-Mb genome sequence and 4, 304 molecular markers. A genomic comparison identified 1, 075 unique gene families in ramie, containing 4, 082 genes. Among these unique genes, five were cellulose synthase genes that were specifically expressed in stem bark, and 3 encoded a WAT 1-related protein, suggesting that they are probably related to high bast fiber yield. An evolutionary analysis detected 106 positively selected genes, 22 of which were related to nitrogen metabolism, indicating that they are probably responsible for the crude protein content and vegetative growth of domesticated varieties. This study is the first to characterize the genome and develop a high-density genetic map of ramie and provides a basis for the genetic and molecular study of this crop.